A faunistic survey on aphids of Marche and Umbria territory in middle-eastern Italy (Bollettino di zoologia agraria e bachicoltura, 2024)
Results are given of a survey carried out on the aphid fauna of the two administrative regions Marche and Umbria in the central-eastern territory of the Italian peninsula. A total number of 312 species and subspecies have been detected there so far, of which 232 species collected in Marche and 246 ones in Umbria countrysides, respectively, Seven out of the totally identified species are new records for the Italian aphid fauna. For each listed species, details are given on host plants, dates and collecting localities related to their findings in each of the two investigated regions. More detailed notes of morphological, taxonomic and biological contents, are added only for the above mentioned new Italian records. Short bio-geographical accounts on the species collected are also reported andcompared either to other regions or the entire Italian territory. Among aphids collected in Marche and Umbria - apart from a fairly percentage of those ones having a southern-European and Mediterranean distribution - there is an almost consistent number of species having an extensive geonemy (i.e. palaearctic and extra-palaearctic representatives). Therefore, it is expected that a number of other species having a more restricted distribution, such as w-palaearctic and European ones, probably remain to be collected in the two investigated regions still.
Keywords: aphid fauna; taxonomy; Marche and Umbria regions; Italy